Hand grip strength in a sample of 11 to 14 years old children. - Carreira, Helena (2010)
The determination of hand grip strength is an objective method of evaluation of upper members' integrity. It is also used as a general health indicator. Data about grip strength values in healthy children is useful in the research and diagnosis of diseases that interfere with grip force. The aim of this study was to determine average values of children hand grip strength by age and evaluate its relation with weight and height.Hand grip strength was measured with the dynamometer Jamar Hydraulic Hand in a convenience sample of 195 children of either gender, with ages between 11 and 14 years old.Statistical significant differences were observed in hand grip strength between genders, being higher in boys. Moderate correlations were found between grip strength and age (R = 0.679, p < 0.001), height (R = 0.691, p < 0.001), and weight (R = 0.620, p < 0.001).The present study presents values of hand grip strength obtained from a sample of Portuguese children of 11 to 14 years old, which are directly associated with height and weight.